Price effects of sovereign debt auctions in the euro-zone: The role of the crisis - Beetsma, Roel; Giuliodori, Massimo; de Jong, Frank; Widijanto, Daniel (Journal of Financial Intermediation, 2016)
We show that new public debt issues cause an auction cycle for Italian secondary-market debt, but not for German debt. The cycle is mainly observed for the crisis period since mid-2007 and is larger when the crisis, as measured by yield volatility and CDS spreads of primary dealers, is more intense. Volatility seems to be the main driving factor. The cycle is also present in secondary-market series with maturities close to the auctioned series. Our findings are consistent with the theory of primary dealers’ limited risk-bearing capacity. There is also weak evidence of spill-overs from foreign auctions to domestic markets.